Biocatalyst development for lactic acid production at acidic pH using inter-generic protoplast fusion - Singhvi, Mamata; Gurjar, Gayatri; Gupta, Vidya; Gokhale, Digambar V. (RSC Advances, 2015)
Global warming and environmental problems force us to develop sustainable processes based on the use of biocatalysts that are eco-friendly with the least potential toxicity. Lactic acid fermentation at neutral pH generates a large amount of gypsum during down-stream processing. Hence it is essential to develop Lactobacillus strains which produce lactic acid at acidic pH thus making the whole downstream process environmentally friendly. Fusant F3 was generated using protoplast fusion between Lactobacillus delbrueckii Mut Uc-3 and Acetobacter pasteurianus NCIM 2314 on solid media at pH 4.0. Fusant F3 was further treated by UV irradiation to generate a mutant, FM1, with improvements in acid tolerance which produced five-fold more lactic acid than the parent strain at acidic pH. The molecular studies using RAPD markers demonstrated that the fusant is derived from both the parental strains, Acetobacter and Lactobacillus and the mutant is derived from the fusant. The utilization of such acid tolerant strains could be able to produce free lactic acid at acidic pH without using neutralizing agents and will offer an effective means for designing environmentally benign processes for lactic acid production.

Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Biodegradation of squalene and n-hexadecane by Gordonia amicalis HS-11 with concomitant formation of biosurfactant and carotenoids - Sowani, Harshada; Deshpande, Ashish; Gupta, Vidya; Kulkarni, Mohan; Zinjarde, Smita (International Biodeterioration & Biodegradation, 2019)
Gordonia amicalis HS-11 has been enriched from a hydrocarbon contaminated tropical soil sample. The ability of this organism to utilize a triterpenic polyunsaturated hydrocarbon, squalene (2,6,10,15,19,23-hexamethyl-6,6,10,14,18,20-tetracosahexane) and the model saturated hydrocarbon n-hexadecane is described here. The isolate degraded squalene and n-hexadecane (79 +/- 3.02 and 96 +/- 4.11%, respectively) after eight days of incubation. The isolate produced an extracellular biosurfactant that reduced surface tension from 69 +/- 2.83 to 40 +/- 1.63 and 35 +/- 2.34 mN m(-1) with squalene and n-hexadecane as carbon sources, respectively, after 6 days. The Actinomycete cleaved squalene to geranylacetone and famesyl acetaldehyde that were further utilized for supporting growth. n-Hexadecane was degraded via monoterminal oxidation and activities of important enzymes (alkane hydroxylase and alcohol dehydrogenase) were highest (215 +/- 8.76 and 169 +/- 6.02 units mg(-1) protein, respectively) after four days. Cells grown on squalene were short and with n-hexadecane there were clumps of longer cells. Squalene and n-hexadecane-grown cell surfaces were smooth possibly due to extracellular surface active compounds. While growing on hydrophobic substrates, some cells were seen adhering to droplets and others were in the free form. The culture was able to simultaneously degrade hydrocarbons and produce two commercially relevant value-added products. The yield of the extracellular biosurfactant on n-hexadecane was 480 mg l(-1) and cells grown on squalene and n-hexadecane also yielded carotenoids (2.3 +/- 0.14 and 2.9 +/- 0.10 mg g(-1) dry cell weight, respectively). This is the first report on the utilization of squalene by Gordonia.
Keywords: Aerobic biodegradation; Carotenoids; Catabolic pathways; Emulsifier; Gordonia amicalis HS-11